Attitudes of kindergarten students towards employing augmented reality technology in teaching (Journal of the College of Basic Education, 2024)
The aim of the current research is to reveal the attitudes of students in the kindergarten department towards employing augmented reality technology in teaching. Many of the current research are on comparative descriptive options, where the innovator of the research consisted of (200) female students from the kindergarten department in the College of Basic Education, Al-Mustansiriya University, where it was conducted. Choosing the sample in a way, the measurement tools represented in the preparation of the questionnaire, the attitudes of female students in the kindergarten department in employing augmented reality technology in Colorado, where the researcher measured (Al-Muzain, 2020) and the paragraphs were modified to suit the research. The results reached in the current research indicated that there are significant differences. Statistical significance among female students in the kindergarten department towards applying augmented reality technology in teaching according to the study tripThe research recommended that the scientific committees in kindergartens prepare and provide additional educational curricula that focus on how to employ and use augmented reality technology in teaching, in addition to training teachers and trainees in the field of kindergartens on how to use technology and augmented reality applications effectively in classrooms.